La opinión del alumnado de la Facultad de Educación (UCM) acerca de la metodología docente - Oliveros Martín-vares, Laura; Ruiz de Miguel, Covadonga (Revista Complutense de Educación, 2006)
This paper presents the opinion the students have about the teaching strategies that university teachers use and also to identify the differences we can find based on characteristics such as gender, studies and the level the students are matriculated. A questionnaire has been done and applied to 254 students who study at the Faculty of Education of the Complutense University in Madrid. The statistic analysis carried out with all those data reveals evident preferences on the part of students towards some fixed methodological options, as well as differences in the independent variables already mentioned.